Cross-Cultural Representations of Musical Shape - Athanasopoulos, George; Moran, Nikki (Empirical Musicology Review, 2013)
In cross-cultural research involving performers from distinct cultural backgrounds (U.K., Japan, Papua New Guinea), we examined 75 musicians’ associations between musical sound and shape, and saw pronounced differences between groups. Participants heard short stimuli varying in pitch contour and were asked to represent these visually on paper, with the instruction that if another community member saw the marks they should be able to connect them with the sounds. Participants from the U.K. group produced consistent symbolic representations, which involved depicting the passage of time from left-to-right. Japanese participants unfamiliar with English language and western standard notation provided responses comparable to the U.K. group’s. The majority opted to use a horizontal timeline, whilst a minority of traditional Japanese musicians produced unique responses with time represented vertically. The last group, a non-literate Papua New Guinean tribe known as BenaBena, produced a majority of iconic responses which did not follow the time versus pitch contour model, but highlighted musical qualities other than the parameters intentionally varied in the investigation, focusing on hue and loudness. The participants’ responses point to profoundly different ‘norms’ of musical shape association, which may be linked to literacy and to the functional role of music in a community.